Kualitas Hidup Remaja Berstatus Sosial Ekonomi Rendah: Bagaimana Kontribusi Resiliensi Keluarga? - Fathin Nazifa Ramadhanty; Melok Roro Kinanthi (Psympathic : Jurnal Ilmiah Psikologi, 2021)
Adolescents from low socioeconomic status are prone to have poor quality of life. To gain optimal functioning, it is important to ensure they experience good quality of life. This study aims to examine whether family resilience affect quality of life among adolescent from low socioeconomic status in Jakarta.  There were 130 participants in this quantitative study. Convenience sampling were applied to select participants. We used Indonesian version of WHOQoLBREF to assess quality of life and Walsh Family Resilience Questionnaire to assess family resilience.  Data were analyzed by regression analysis and stated family resilience has significant positively contribution to quality of life among participants. For each dimension, the contribution of family resilience to quality of life was 7% to 16.4%. It may indicate that family strength-based approach should be added in developing intervention to enhance quality of life among adolescents from low socioeconomic status in Jakarta.